Dopaminergic REST is implicated in the tamoxifen-induced neuroprotection against manganese toxicity in female mice - Pajarillo, Edward; Digman, Alexis; Ajayi, Itunu; Kim, Sanghoon; Son, Deok-Soo; Aschner, Michael; Lee, Eunsook (Frontiers in Pharmacology, 2025)
IntroductionChronic manganese (Mn) overexposure causes manganism, a Parkinson’s disease-like neurological disorder, due to its preferential accumulation in the basal ganglia. Tamoxifen (TX), a selective estrogen receptor modulator (SERM), afforded neuroprotection against Mn toxicity, and RE1-silencing transcription factor (REST) in dopaminergic neurons mitigated Mn-induced neurotoxicity.MethodsThis study investigated whether dopaminergic REST played a role in TX’s protection against Mn toxicity in the nigrostriatal regions using wild-type (WT) and dopaminergic REST-deleted (REST cKO) female mice. Behavioral studies, including open-field, rotarod, and novel object recognition tests, were conducted with molecular biology assays.ResultsTX mitigated Mn-induced deficits in several motor functions and cognition, as well as dopaminergic neuronal injury, parallel with the attenuation of Mn-decreased tyrosine hydroxylase (TH) and Mn-increased proapoptotic Bax in REST cKO mice. However, several Mn-dysregulated genes associated with oxidative stress and mitochondrial function, including catalase, superoxide dismutase 2 (SOD2), and optic atrophy 1 (OPA1), were attenuated by TX only in WT, but not in REST cKO. At the epigenetic levels, TX attenuated Mn-reduced acetylation of H3K27 in both WT and REST cKO, but Mn-decreased H3K27ac interaction with promoters of catalase, SOD2, and OPA1 was attenuated by TX only in WT, not REST cKO. TX attenuated Mn-decreased estrogen receptor (ER)-α and ER-β protein levels in both WT and REST cKO mice.DiscussionOur findings suggest that TX significantly attenuated Mn-induced TH reduction and behavioral deficits in REST cKO, not to the levels of its protection in WT, since several genes involved in TX-induced protective pathways required dopaminergic REST. Taken together, while TX has some REST-independent protective effects, dopaminergic REST is critical for full neuroprotection.